1999
DOI: 10.1007/s004030050396
|View full text |Cite
|
Sign up to set email alerts
|

UV irradiation induces downregulation of bcl-2 expression in vitro and in vivo

Abstract: Recently, the proto-oncogenes bcl-2 and bax have emerged as important regulators of the apoptotic form of cell death. We examined UV irradiation-elicited apoptosis and regulation of bcl-2 and bax expression both in vivo in human skin and in vitro in HeLa cells. Using flow cytometric analysis, HeLa cells were found to undergo apoptosis at the 12-h time-point after exposure to UVB irradiation (100 mJ/cm2). The expression of bcl-2 mRNA was found to decrease after a single dose of UVB radiation (doses 10-200 mJ/cm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 25 publications
3
27
0
1
Order By: Relevance
“…It has also been demonstrated that the level of the antiapoptotic protein Bcl-2 is downregulated following UV exposure and that this contributes to UV-induced apoptosis (Isoherranen et al, 1999;Washio et al, 1999;Dunkern et al, 2001). The Bcl-2 gene promoter has been shown to bind E2F1 and to be transcriptionally activated by E2F1 overexpression (Gomez-Manzano et al, 2001).…”
Section: E2f1 Status Does Not Affect Activation Of Mitogenactivated Pmentioning
confidence: 99%
“…It has also been demonstrated that the level of the antiapoptotic protein Bcl-2 is downregulated following UV exposure and that this contributes to UV-induced apoptosis (Isoherranen et al, 1999;Washio et al, 1999;Dunkern et al, 2001). The Bcl-2 gene promoter has been shown to bind E2F1 and to be transcriptionally activated by E2F1 overexpression (Gomez-Manzano et al, 2001).…”
Section: E2f1 Status Does Not Affect Activation Of Mitogenactivated Pmentioning
confidence: 99%
“…The anti-apoptotic bcl-2 protein is known to decrease after UVB irradiation, and its decrease has been correlated the induction of UVB-induced apoptosis (40). A431 cells were therefore UVB irradiated with low and intermediate doses and at 1, 2, and 3 h after irradiation cell lysates were tested for bcl-2 expression.…”
Section: Bcl-2 Persists During the Delay Of The Executioner Phase Of mentioning
confidence: 99%
“…In many systems, UV irradiation triggers p53 phosphorylation which in turn activates proapoptotic genes and induces apoptosis through mitochondria [6]. In addition, it has been shown that UV irradiation induces apoptosis by downregulating Bcl-2 [39]. We examined the ability of UV to induce apoptosis in GK and HeLa cells.…”
Section: Discussionmentioning
confidence: 99%